2009
DOI: 10.5465/amr.34.4.zok689
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Path Dependence: Opening the Black Box

Abstract: To enable a better understanding of the underlying logic of path dependence, we set forth a theoretical framework explaining how organizations become path dependent. At its core are the dynamics of self-reinforcing mechanisms, which are likely to lead an organization into a lock-in. By drawing on studies of technological paths, we conceptualize the emergent process of path dependence along three distinct stages. We also use the model to explore breakouts from organizational path dependence and discuss implicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
181
1
23

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 303 publications
(208 citation statements)
references
References 78 publications
3
181
1
23
Order By: Relevance
“…In this case, high absorptive capacity can help in "selecting and linking" different types of knowledge (Winter, 2003), along well-known paths. This can reinforce habitual action patterns (Dosi et al, 2000) that further deepen path dependence where actions become self-reinforcing processes (Schreyögg and Kliesch-Eberl, 2007;Sydow et al, 2009). Knowledge accumulation from multiple and novel external sources, therefore, helps to deepen the firm's existing knowledge bases but does not necessarily breed variety.…”
Section: The Role Of Absorptive Capacitymentioning
confidence: 83%
“…In this case, high absorptive capacity can help in "selecting and linking" different types of knowledge (Winter, 2003), along well-known paths. This can reinforce habitual action patterns (Dosi et al, 2000) that further deepen path dependence where actions become self-reinforcing processes (Schreyögg and Kliesch-Eberl, 2007;Sydow et al, 2009). Knowledge accumulation from multiple and novel external sources, therefore, helps to deepen the firm's existing knowledge bases but does not necessarily breed variety.…”
Section: The Role Of Absorptive Capacitymentioning
confidence: 83%
“…This includes the question of whether this shift is triggered more by actual field changes that force an organization to adapt or by a change in an organization's interpretation of its environment. Associated topics include the lock-in of organizations, the creation of new organizational paths [34][35][36] as well as sectoral adaptability to technological changes [37].…”
Section: Conclusion and Research Outlookmentioning
confidence: 99%
“…Experiences of successful actions are therefore valuable for the growth-aspiring SME. Previous research has shown that repetitive behavior, however, might lead to learning myopia (Levinthal and March 1993;Tsang 2002) and the Blockin^phenomenon (Sydow et al 2009). In cases where a particular outcome reproduction is the result of one particular predominant action pattern, the firm risks to lose its capability to adopt better alternatives and might become path dependent.…”
Section: International Opportunity Scouting and Opportunity Noveltymentioning
confidence: 99%